Virtual screening and drug repositioning of FDA-approved drugs from the ZINC database to identify the potential hTERT inhibitors - Afzaal, Hasan; Altaf, Reem; Ilyas, Umair; Zaman, Shaiq Uz; Abbas Hamdani, Syed Damin; Khan, Saifullah; Zafar, Hajra; Babar, Mustafeez Mujtaba; Duan, Yongtao (Frontiers in Pharmacology, 2022)
The length of the telomeres is maintained with the help of the enzyme telomerase constituting of two components, namely, a core reverse transcriptase protein (hTERT) and RNA (hTR). It serves as a significant and universal cancer target. In silico approaches play a crucial role in accelerating drug development processes, especially cancer drug repurposing is an attractive approach. The current study is aimed at the repurposing of FDA-approved drugs for their potential role as hTERT inhibitors. Accordingly, a library of 2,915 sets of FDA-approved drugs was generated from the ZINC database in order to screen for novel hTERT inhibitors; later on, these were subjected to molecular docking analysis. The top two hits, ZINC03784182 and ZINC01530694, were shortlisted for molecular dynamic simulation studies at 100 ns based on their binding scores. The RMSD, RMSF, Rg, SASA, and interaction energies were calculated for a 100-ns simulation period. The hit compounds were also analyzed for antitumor activity, and the results revealed promising cytotoxic activities of these compounds. The study has revealed the potential application of these drugs as antitumor agents that can be useful in treating cancer and can serve as lead compounds for further in vivo, in vitro, and clinical studies.